Anti-inflammatory polymer electrodes for glial scar treatment: bringing the conceptual idea to future results - Asplund, Maria; Boehler, Christian; Stieglitz, Thomas (Frontiers in Neuroengineering, 2014)
Conducting polymer films offer a convenient route for the functionalization of implantable microelectrodes without compromising their performance as excellent recording units. A micron thick coating, deposited on the surface of a regular metallic electrode, can elute anti-inflammatory drugs for the treatment of glial scarring as well as growth factors for the support of surrounding neurons. Electroactivation of the polymer drives the release of the substance and should ideally provide a reliable method for controlling quantity and timing of release. Driving signals in the form of a constant potential, a slow redox sweep or a fast pulse are all represented in literature. Few studies present such release in vivo from actual recording and stimulating microelectronic devices. It is essential to bridge the gap between studies based on release in vitro, and the intended application, which would mean release into living and highly delicate tissue. In the biological setting, signals are limited both by available electronics and by the biological safety. Driving signals must not be harmful to tissue and also not activate the tissue in an uncontrolled manner. This review aims at shedding more light on how to select appropriate driving parameters for the polymer electrodes for the in vivo setting. It brings together information regarding activation thresholds for neurons, as well as injury thresholds, and puts this into context with what is known about efficient driving of release from conducting polymer films.